(3cfR GdOQQ hLGeY GdZQQs - (3CHh HcQ Hf YHO Gddg Hf CjHc, GdeYQha HGHf GdOhGOGQqj (B( (3UGMH UQNO (B)(3,J (B736 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi dGJQGg GdYjhf HeTGgOI GdYjGf s
(3BNQgG (B:s
(3jfJgi HPcQ bGJd Ydi QVi Gddg Yfg s
(3bSe GdeDda GdcJGH Edi CLRGA CaQO dcd OhdI LRAG hCWdb Ydjg GSeGs
(3cGf GdeDda MjG SfI (B736 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B66 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B65s
Keywords: (3GdJGQjNs